Slc38a1 Conveys Astroglia-Derived Glutamine into GABAergic Interneurons for Neurotransmitter GABA Synthesis - Tayyaba Qureshi (Cells, 2020)
GABA signaling is involved in a wide range of neuronal functions, such as synchronization of action potential firing, synaptic plasticity and neuronal development. Sustained GABA signaling requires efficient mechanisms for the replenishment of the neurotransmitter pool of GABA. The prevailing theory is that exocytotically released GABA may be transported into perisynaptic astroglia and converted to glutamine, which is then shuttled back to the neurons for resynthesis of GABA—i.e., the glutamate/GABA-glutamine (GGG) cycle. However, an unequivocal demonstration of astroglia-to-nerve terminal transport of glutamine and the contribution of astroglia-derived glutamine to neurotransmitter GABA synthesis is lacking. By genetic inactivation of the amino acid transporter Solute carrier 38 member a1 (Slc38a1)—which is enriched on parvalbumin+ GABAergic neurons—and by intraperitoneal injection of radiolabeled acetate (which is metabolized to glutamine in astroglial cells), we show that Slc38a1 mediates import of astroglia-derived glutamine into GABAergic neurons for synthesis of GABA. In brain slices, we demonstrate the role of Slc38a1 for the uptake of glutamine specifically into GABAergic nerve terminals for the synthesis of GABA depending on demand and glutamine supply. Thus, while leaving room for other pathways, our study demonstrates a key role of Slc38a1 for newly formed GABA, in harmony with the existence of a GGG cycle.